The Religious Market in Contemporary Indonesia: A Case Study of the Eden-Salamullah Group - Halimatussa'diyah, Iim (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
In sociology-or more correctly sociology of religion - there exists a theory which views religion as an economic commodity. That is to say, religion is a commodity which is produced and marketed in a religious market. This theory is known as the supply-side approach. The idea of applying an economic concept to religion has been promoted by many sociologists particularly the likes of Bain-bridge, Finke, Iannaccone, and Stark. This paper examines the application of the supply-side approach, with particular focus on its application in the Indonesian context (with reference to Islam). We will further consider the possibility of the eventuation of a triple market in Indonesia, drawing on a case study of the Eden-Salamullah group.DOI: 10.15408/sdi.v15i1.538